Pengaruh Kenaikan Pajak Pertambahan Nilai (PPN) dan Inflasi Terhadap Volume Penjualan Studi Kasus pada PT Astra International Tbk Tahun 2022 - 2024 - Sulis Mutiara Zulfa; Daryanto Daryanto; Daniel Imanuel Manafe (Dharma Ekonomi, 2026)
This study aims to analyze the impact of the increase in Value Added Tax (VAT) and inflation on the sales revenue of PT Astra International Tbk during the 2022–2024 period. The research employs a quantitative approach using multiple regression analysis to examine the relationship between VAT, inflation, and sales revenue. Secondary data were obtained from the company’s financial statements, inflation data from Statistics Indonesia (BPS), and VAT rate information from the Directorate General of Taxes (DJP). The data were analyzed to identify how VAT and inflation influence the company’s revenue. The results indicate that both VAT and inflation have a significant effect on sales revenue, both simultaneously and partially. The coefficient of determination (R²) of 0.899 shows that 89.9% of the variation in sales revenue is explained by the changes in VAT and inflation rates. These findings suggest that VAT and inflation are important economic factors that should be considered by businesses, especially in the automotive industry, when planning strategies for revenue generation. Furthermore, the study emphasizes the critical need for companies to adapt to changing fiscal policies and macroeconomic conditions to maintain profitability and competitive advantage in a fluctuating economic environment.